Effects of Damaged Levels and Pruning of Peach and Japanese Apricot Trees by Hailstorms on the Performance - Byeong-Sam Kim; Hye-Sung Cho; Kyung-Chul Cho; Hyo-Jung Kim; Bo-Bae Lee; Mengmeng Gu; Hyun-Sug Choi (Agronomy, 2021)
Defoliation (DF) on peach (Prunus persica L.) and Japanese apricot (Prunus mume Sieb. et Zucc.) trees caused by a hailstorm in 2017, year 1, was investigated for its effects on growth and fruit yield in South Korea over four years, comparing with recovery effects of the DF trees treated with repeated immediate pruning (IP) right after the storm. Treatments included 0–10, 10–40, 40–70, and 70–100% of DF trees, with 0–10, 10–40, 40–70, and 70–100% of DF + IP trees. The hailstorms increased the damages to shoots for peaches and to shoots and scaffold for Japanese apricot trees in year 1, with fruit yield reduced more than 80% observed on 10–100 DF of both fruit species. The IP treatment increased the number of new shoots in years 2–4 but reduced shoot length and diameter of peach and Japanese apricot trees. Tree canopy in years 2–4 was reduced on 40–100 DF of peach trees and on 70–100 of DF and DF + IP of Japanese apricot trees. The 40–100 DF Japanese apricot trees resulted in a fruit yield index of less than 90% for years 2–4, which was observed on 40–100 DF+IP trees only in year 2 due to balanced tree vegetative and reproductive growth.